Homozygous familial hypercholesterolemia in childhood: Genotype-phenotype description, established therapies and perspectives. (April 2016) - Sanna, Claudia; Stéphenne, Xavier; Revencu, Nicole; Smets, Françoise; Sassolas, Agnes; Di Filippo, Mathilde; Descamps, Olivier S.; Sokal, Etienne M.
Abstract: Familial hypercholesterolemia (FH) is a co-dominantly inherited disorder of plasma lipoprotein metabolism. The prevalence of heterozygous FH (HeFH) is between 1/500 and 1/200 whereas that of homozygous form (HoFH) is about 1/1, 000, 000. Diagnosis is based on cutaneous xanthomas and untreated levels of LDL-cholesterol over 500 mg/dl before 10 years of age. Life expectancy, without treatment, does not exceed 20 years of age. The aim of this study is to characterise in details a cohort of 8 HoFH paediatric patients in order to illustrate all the current therapeutic options and to add some clinical and genetic information about this rare disease. We collected demographic, clinical, biological, imaging and genotype details. Furthermore, clinical and biochemical response to different treatment methods was retrospectively evaluated. All patients had genetically proven HoFH. All patients were subject to a lipid-lowering diet and medical treatment (except one), three patients underwent a liver transplant and one an hepatocytes infusion. Medical treatment was well tolerated with a median reduction of 44% and 47% in LDL-Cholesterol and Total Cholesterol respectively. The hepatocytes transplant produced a further, though slight, decrease in cholesterol levels as opposed to medical therapy alone. Transplanted patients normalized their cholesterol levels. Since the very high cardiovascular risk, HoFH requires immediate diagnosis, treatment and monitoring. Nowadays, the use of statins remains the cornerstone of medical therapy and liver transplantation is the possibly curative therapy. Besides, high hopes are pinned in new drugs (antibody targeting PCSK9, Mipomersen and Lomitapide) and stem cells. Highlights: We characterised in details 8 HoFH paediatric patients. We describe all the therapeutic options and clinical/genetic information. Currently statins remains the cornerstone of medical therapy. Liver transplantation may be considered as a possibly curative therapy. High hopes are pinned in stem cells and new drugs like antibody targeting PCSK9.